O papel das tecnologias digitais na educação: perspectivas para além dos muros da escola - Fabio Fernando Kobs; Eloy Fassi Casagrande Júnior (Centro Universitário Salesiano de São Paulo, 2016)
This article presents as a research problem to identify how digital technologies can be present in education, and how teachers and the school can adjust to the new generation of students. It has a positive affirmative case, where assumes that the use of digital technologies can help in the education of young people and adolescents. Thus, the objective of this article is to ascertain some possibilities in the extension of digital technologies to the education of young people and adolescents. The classification of the article in the form of approach to the problem and the methods used, is classified as literature. Exposes the concepts of Internet and digital technologies, bringing the Internet numbers in Brazil and demonstrating digital technologies and the Internet in education. The article exposed suggestions and strategies for teachers in the digital age; brought arguments to change the educational system; presented the benefits obtained with mobile learning; and also recommendations for teaching the new generation of students. Still, through the role of digital technologies in education, evidence of how digital technologies can be present in education and positively.